The Effect of Financial Distress, Capital Intensity, Political Cost, And Company Size Against Accounting Conservatism - Prayoga, Anggie; Eliza, Any; Kurniawan, Agus (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This research aims to analyze the influence of Financial Distress, Capital Intensity, Political Cost, and Company Size on Accounting Conservatism in manufacturing companies listed on the Jakarta Islamic Index from 2019 to 2023. A quantitative approach was employed using secondary data sourced from the financial statements of manufacturing companies listed on the Jakarta Islamic Index, published by the companies and the Indonesia Stock Exchange. The data were analyzed using panel data regression with the Fixed Effect Model (FEM). The results of the study indicate that Financial Distress, Political Cost, and Capital Intensity do not have a significant effect on Accounting Conservatism, while Company Size does have an effect on Accounting Conservatism. However, Financial Distress, Capital Intensity, Political Cost, and Company Size collectively have an influence on Accounting Conservatism.